Resource Acquisition in the Emergence Phase: Considering the Effects of Embeddedness and Resource Dependence - Newbert, Scott L.; Tornikoski, Erno T. (Entrepreneurship Theory and Practice, 2013)
Despite evidence that embedded ties are important to entrepreneurs seeking low–cost resources, no research to date has explored how this relationship unfolds in the context of emerging organizations, how the inevitable dependence on ties might drive up resource acquisition costs, or how the manner in which ties are embedded might affect the specificity of these resources. We develop a conceptual model that examines these relationships and, analyzing data from the Panel Study of Entrepreneurial Dynamics I, find support for the majority of our hypotheses. We then discuss the implications of our findings for scholars and practitioners.